Maternal high fat intake affects the development and transcriptional profile of fetal intestine in late gestation using pig model. Issue 1 (December 2016) - Che, Lianqiang; Liu, Peilin; Yang, Zhengguo; Che, Long; Hu, Liang; Qin, Linlin; Wang, Ru; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Feng, Bin; Li, Jian; et al.
Abstract Background The objective of this study was to investigate the effects of maternal high fat intake on intestinal development and transcriptional profile. Methods Eight gilts with similar age and body weight were randomly allocated into 2 groups receiving the control and high fat diets (HF diet) from d 30 to 90 of gestation, with 4 gilts each group and one gilt each pen. At d 90 of gestation, two fetuses each gilt were removed by cesarean section. Intestinal samples were collected for analysis of morphology, enzyme activities and transcriptional profile. Results The results showed that feeding HF diet markedly increased the fetal weight and lactase activity, also tended to increase intestinal morphology. Porcine Oligo Microarray analysis indicated that feeding HF diet inhibited 64 % of genes (39 genes down-regulated while 22 genes up-regulated), which were related to immune response, cancer and metabolism, also markedly modified 33 signal pathways such as antigen processing and presentation, intestinal immune network for IgA production, Jak-STAT and TGF-ß signaling transductions, pathways in colorectal cancer and glycerolipid metabolism. Conclusion Collectively, it could be concluded that maternal high fat intake was able to increase fetal weight and lactase activity, however, it altered the intestinal immune response, signal transduction and metabolism.